Immunotoxicity induced by pesticides in humans - Souza, Rayane Cristina; Santos, Elinaura Pereira dos; Fontenelle, Pedro Henrique Cunha; Castelo Branco, Thaís de Melo; Santos, Samia Melo; Falcai, Angela (Ciência e Natura, 2022)
The evidence that the immune system is affected by pesticides is growing and indicates that pesticide exposure has detrimental health effects and can contribute to increased risksfor long-term diseases, including different types of psychiatric disorders, cancers, allergies, autoimmune diseases, and infectious diseases. Motivated by such studies, the present review highlights mechanisms involved in the immunological toxicity of pesticides, as well as the association between pesticide exposure and the predisposition of diseases, caused by perturbation of immune system function. A literature review was performed using the MEDLINE, PubMed, and Scopus databases with publication dates from 1986 to 2016. The following descriptors were used: “immunotoxicity”,“Pesticides”, and“immune system”. Pesticides can affect host resistance and can directly affect lymphoid tissues and/or native cells. Disorders such as immunosuppression, hypersensitivity, autoimmunity, and cancers have been cited to result from changes in the immune system. Although public health concerns regarding pesticide exposures are directed primarily at carcinogenic and neurological mutations, these compounds can cause profound effects on the immune system and may trigger several other processes by disruption of function in other physiological systems.